Метан в поверхностных водах окраинных морей Евразии; Доклады Академии наук; Т. 465, № 4 - Космач Д. А. Денис Алексеевич; Сергиенко В. И.; Дударев О. В. Олег Викторович; Куриленко А. В.; Густафсон О.; Семилетов И. П. Игорь Петрович; Шахова Н. Е. Наталья Евгеньевна (2015, 2015)
Заглавие с экрана